Estudo do fator de segurança de um aterro sanitário tipo convencional comparando com um aterro sanitário tipo encosta - Andrades, Silvana Alves de (2018)
The growth of human population allied with the social economic development provided changes in the world habits, specially involving the exacerbated consume of goods that has increased the generation of waste. In consequence, the management and final destination of this waste become a giant issue to be faced. Nowadays one of the most used methods of final disposal are the sanitary landfills. Appropriate places for those sanitary landfills are getting harder to find specially in big urban centers and under the stricter control of Environmental Departments and Environmental Laws. So, optimize the lifetime of the existing sanitary landfills has become one of the main focus of the City and State managers. One strategy used to optimize the lifetime is to extend its area. On a sanitary landfill enlargement it is vital that this extension is projected a monitored correctly, if not, landslides may happen, exposing the waste of the sanitary landfills resulting in an environmental disaster. The most efficient way to decrease this risk is the geotechnical monitoring of the waste mass stability. In face of this situation, this present document presents, using mathematic simulation models a way to estimate the slope stability and safety factor of conventional and hillside sanitary landfills. The specific goals of this document are, to calculate the stability safety factor of the sanitary landfill located at the metropolitan region of Curitiba, and to calculate the stability safety factor of the sanitary landfill at the metropolitan region of São Paulo, both during the period from August 2014 until August 2015, using software Slide 6 and Slope W. As an additional goal of this study, it was stablished a parallel between the safety factor value compared with the precipitation levels and leachate flow of the studied landfills. This study has permitted to state that, although the cause effect relation is clear, the relations between precipitation, leachate flow and safety factor is not expressive. However, there is a significant correlation between the leachate level and the safety factor, once both variables are a fundamental data in the modelling process. The sanitary landfill located at the metropolitan region of Curitiba, constructed under the conventional landfill method, has presented most stable safety factors that the landfill located at the metropolitan region of São Paulo, constructed under the Hillside landfill method. This result was reveal by the modelling made with the software Slide 6 and also by the modeling made using the software Slope W.